2003
DOI: 10.1620/tjem.201.239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rho and Rho-Dependent Kinase in Serotonin-Induced Contraction Observed in Bovine Middle Cerebral Artery

Abstract: The current study was designed to characterize the role of Rho and Rho-dependent kinase (Rho-kinase) in isometric contractile responses induced by serotonin (5-HT) and a solution containing 40 mM K(+) (high K(+)) in ring preparations of the middle cerebral artery of bovine. Application of W-7, a Ca(2+)-calmodulin inhibitor, reversibly and equally attenuated the amplitudes of contractions produced by both 5-HT and high K(+). Similar effects were observed with ML-7, an inhibitor of myosin light chain kinase. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Relatively few studies have examined the functional importance of Rho-kinase in cerebral circulation, but recent evidence suggests that this signaling pathway mediates vasoconstrictor responses to serotonin, endothelin-1, UTP, and oxyhemoglobin (Miao et al, 2002;Nishikawa et al, 2003;Wickman et al, 2003;Luykenaar et al, 2004).…”
Section: Constrictor Responses Of Cerebral Arteries To Angiotensin IImentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few studies have examined the functional importance of Rho-kinase in cerebral circulation, but recent evidence suggests that this signaling pathway mediates vasoconstrictor responses to serotonin, endothelin-1, UTP, and oxyhemoglobin (Miao et al, 2002;Nishikawa et al, 2003;Wickman et al, 2003;Luykenaar et al, 2004).…”
Section: Constrictor Responses Of Cerebral Arteries To Angiotensin IImentioning
confidence: 99%
“…Second, we examined the role of Rho-kinase in mediating vasoconstriction in response to Ang II. Activation of Rho-kinase is thought to be a key mechanism of calcium sensitization that mediates responses to several vasoconstrictors (Miao et al, 2002;Nishikawa et al, 2003;Wickman et al, 2003;Luykenaar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…20 Another study suggested the activation of Rho A and ROCK in 5-HT-induced contraction of the bovine middle cerebral artery. 21 Serotonin participates in pulmonary hypertension, 5,22,23 and a polymorphism of the 5-HT transporter has been proposed to be involved in pulmonary hypertension in humans. 24 Because agents that block ROCK are currently available 25,26 and may be useful in pulmonary hypertension, [27][28][29] we have undertaken an investigation of the potential participation of ROCK in pulmonary arterial SMC signaling and proliferation produced by 5-HT.…”
mentioning
confidence: 99%
“…For example, activity of rho kinase is thought to be a key mediator of vasoconstrictor responses through effects on calcium sensitization. [17][18][19] Activity of rho kinase may be increased in cerebral blood vessels during disease. 8,20 The precise cause for this increase is not certain but may be a consequence of loss of inhibitory effects of NO on rho kinase or direct effects of ROS to promote activity of rho kinase.…”
mentioning
confidence: 99%